Precision nanoparticles for drug delivery, cell therapy tracking, and theranostics - Felder-Flesch, Delphine; Talamini, Laura; Muller, Sylviane (Comptes Rendus. Chimie, 2024)
For more than two decades, nanoparticles have attracted a great deal of attention from researchers and developers. When properly designed, vectorized nanoparticles represent high-value-added tools with potentially invaluable properties in a number of areas, including biology, biotechnology, and medicine owing to their exceptional physico-chemical properties, especially resulting from their high surface area, high loading capacity, and nanoscale size. Smart design and building of nanoparticles through appropriate surface chemistry and functionalization provide a material that possesses multifunctional capabilities, able to specifically interact with a selected target, release a compound in a controlled and sustained way, and overcome, if desired, biological barriers such as the blood–brain barrier or lung barriers of interest. Unique constructions have thus opened up original and innovative possibilities in biotechnological and biomedical fields such as imaging, biosensors, rapid diagnostics, drug delivery, medical implants, and tissue engineering. This article briefly describes the main types of nanoparticles that have been developed and their advantages and disadvantages depending on the intended application, and highlights some remarkable results achieved recently in the biomedical field. Certain dangers or fears regarding their use in human and animal therapy or for users have been mentioned. Finally, conclusions and future perspectives are provided.